PCU | PSP : uma estratégia que promove agilidade na gerência de projetos de software - Sanchez, Arnaldo Napolitano (Universidade Federal de São Carlos, 2008)
Background: aiming to implement software processes quality models for small companies, several projects were developed in collaboration with Universidade Federal de São Carlos and USP São Carlos research centers. In this context, it was identified the need of improving the process of project management. Aim: this work presents a strategy that facilitates the management of software projects adjusting the Use Case Points method so that it effectively reflects the development team characteristics and the system planning to be developed be close the reality. This adjust comes from the application of the PSP (Personal Software Process) process activities and from a constant evaluation of the activities in course, together the actualization and control of the elaborated project planning. Method: this strategy was extracted from the systematic application of both the PCU method and PSP process, in the small companies’ environment, so that the project progress can be always evaluated. On account of this, it was identified the necessity of adjust the Effort Level (NDE – in Portuguese) per Use Case Point as well as the environmental factors of the PCU method per developer. The monitoring of the project through the PCU method variables adjustment, based on the PSP activities, resulted in the definition of the PCU|PSP Strategy, proposed here. Results: the strategy is being actually applied in small software companies, as shown in the two case studies presented in this work. The obtained results indicate its contribution to the quality improvement of the management software projects, mainly in relation to the planning and control activities. Conclusion: based on the obtained results, the strategy has achieved the objective of facilitating the implementation of process quality models, like the MPS.BR, only in respect to project management. Besides, the strategy is perfectly adjusted to the Scrum agile method, making agile and controllable the project management, what is a positive point, mainly in the context of small companies.
PCU | PSP : a strategy that promotes agility in software project management
UCP | PSP : una estrategia que promueve la agilidad en la gestión de proyectos de software
Keywords: Pontos por Casos de Uso; Gerenciamento de projetos de software; Personal Software Process; Management of software projects; Use case points; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO